Xenobiotic Metabolizing Gene Variants and Renal Cell Cancer: A Multicenter Study - Heck, Julia E.; Moore, Lee; Lee, Yuan-Chin Amy; McKay, James; Hung, Rayjean; Karami, Sara; Gaborieau, Valérie; Szeszenia-Dabrowska, Neonila; Zaridze, David; Mukeriya, Anush; Mates, Dana; Foretova, Lenka; et al. (Frontiers in Oncology, 2012)
Background: The countries of Central and Eastern Europe have among the highest worldwide rates of renal cell cancer. Few studies have examined whether genetic variation in xenobiotic metabolic pathway genes may modify risk for this cancer. Methods: The Central and Eastern Europe Renal Cell Cancer (RCC) study was a hospital-based case-control study conducted between 1998 and 2003 across seven centers in Central and Eastern Europe. Detailed data were collected from 874 cases and 2053 controls on demographics, work history and occupational exposure to chemical agents. Genes (cytochrome P-450 family, N-acetyltransferases, NAD(P)H:quinone oxidoreductase I (NQO1), microsomal epoxide hydrolase (mEH), catechol-O-methyltransferase (COMT), uridine diphosphate-glucuronosyltransferase (UGT)) were selected for the present analysis based on their putative role in xenobiotic metabolism. Haplotypes were calculated using fastPhase. Odds ratios (OR) and 95% confidence intervals (CI) were estimated by unconditional logistic regression adjusted for country of residence, age, and sex. Results: We observed an increased risk of renal cell cancer (RCC) with three SNPs. After adjustment for multiple comparisons no associations remained significant. In haplotype analyses, the NAT1*14A phenotype was associated with increased risk of RCC (OR=1.71, 95% CI 1.02, 2.87) in comparison to all other phenotypes, a finding that should be taken with caution. NAT2 slow acetylation was not associated with disease. Conclusion: We observed no association between this pathway and renal cell cancer.